Development of pico-satellite – solar energy based power supply system - Soon, Charlie Jing Jun. (2010)
The objective of this project is to develop a solar energy based power supply system for a pico-satellite. Currently, commercial ready pico-satellite power systems are available but are costly and of fixed specifications that might not meet the requirements of the desired mission. The pico-satellite power supply system consists of three main modules. They are the solar array module, power distribution module and battery management module. In this project, the solar array module uses the Spectrolab improved triple junction solar cell and its characteristic is simulated using a solar array simulator. The solar array simulator has been programmed to take into account the operation scenario in the space. Factors that affect the solar I-V characteristics have been considered such as the variation of solar cell temperature and the angle of incident from the sun. For the power distribution module, it was designed to step down the voltage with efficiency up to 94% from the battery or solar array before distributing the power to the payloads. An electronic load was used to simulate the payloads. Protection circuits are also designed in this module to protect the payloads. Lastly, the battery charging controller developed in the system plays the role of charging and managing the batteries. The final product designed is able to supply output voltage levels of 3.3V and 5.0V with voltage and current ripple of 2.88% and 3.2% at full load. The maximum achievable efficiency is 83% when both step down converter is loaded at 400mA and 77% when full load. Besides that, the protection circuit can be tuned to the desired payloads max current to protect the payload. The response time of the protection circuit is about 753.63μs. Temperature sensing circuit and data acquisition circuit had also been incooperated into the system.